Human CD133 + Progenitor Cells Promote the Healing of Diabetic Ischemic Ulcers by Paracrine Stimulation of Angiogenesis and Activation of Wnt Signaling - Lucíola S. Barcelos; Cécile Duplàa; Nicolle Kränkel; Gallia Graiani; Gloria Invernici; Rajesh Katare; Mauro Siragusa; Marco Meloni; Ilaria Campesi; Manuela Monica; Andreas Simm; Paola Campagnolo; et al. (2009)
We evaluated the healing potential of human fetal aorta-derived CD133 + progenitor cells and their conditioned medium (CD133 + CCM) in a new model of ischemic diabetic ulcer. Streptozotocin-induced diabetic mice underwent bilateral limb ischemia and wounding. One wound was covered with collagen containing 2×10 4 CD133 + or CD133 − cells or vehicle. The contralateral wound, covered with only collagen, served as control. Fetal CD133 + cells expressed high levels of wingless ( Wnt ) genes, which were downregulated following differentiation into CD133 − cells along with upregulation of Wnt antagonists secreted frizzled-related protein (sFRP)-1, -3, and -4. CD133 + cells accelerated wound closure as compared with CD133 − or vehicle and promoted angiogenesis through stimulation of endothelial cell proliferation, migration, and survival by paracrine effects. CD133 + cells secreted high levels of vascular endothelial growth factor (VEGF)-A and interleukin (IL)-8. Consistently, CD133 + CCM accelerated wound closure and reparative angiogenesis, with this action abrogated by coadministering the Wnt antagonist sFRP-1 or neutralizing antibodies against VEGF-A or IL-8. In vitro, these effects were recapitulated following exposure of high-glucose-primed human umbilical vein endothelial cells to CD133 + CCM, resulting in stimulation of migration, angiogenesis-like network formation and induction of Wnt expression. The promigratory and proangiogenic effect of CD133 + CCM was blunted by sFRP-1, as well as antibodies against VEGF-A or IL-8. CD133 + cells stimulate wound healing by paracrine mechanisms that activate Wnt signaling pathway in recipients. These preclinical findings open new perspectives for the cure of diabetic ulcers.